62. Sensory Tricks in cervical dystonia: A neurophysiological study with short latency afferent inhibition. Issue 4 (April 2016) - Bianchi, F.; Amadio, S.; Cursi, M.; Urban, I.P.; Butera, C.; Guerriero, R.; Comi, G.; Carro, U. Del
Abstract : A classic hallmark of cervical dystonia (CD) is the improvement of dystonic symptoms during a specific maneuver, defined 'sensory trick' (ST). Even if the mechanism by which ST improves dystonia is not well understood, it is likely that cortical sensorimotor integration processes are involved. In a previous preliminary study, we evaluated the short latency afferent inhibition (SAI) in a group of CD patients and the effects of ST on the SAI profile. To date, we have increased our sample including 28 patients with primary CD (18 with ST, CD+, and 10 without ST, CD-) and 11 controls. The analysis of variance showed no significant differences between CD- patients and controls. On the contrary, a remarkable trend toward a reduced SAI was observed in CD+ patients when they did not perform ST. Interestingly, SAI was further reduced in CD+ patients when they performed ST, reaching a strong statistical relevance. Our results show the presence of an abnormal sensorimotor integration in CD+ patients. Furthermore, they prove that ST acts by modulating the abnormal link between sensory input and motor output.